The Lying Game - Ware, Ruth (New York : Scout Press, 2017)
Four girls are best friends and inseparable at Salten, a second-rate boarding school near the cliffs of the England Channel. They are notorious for playing the Lying Game, telling lies to both fellow boarders and faculty. Their little game has consequences when they soon learn their shared past was not as safely buried as they had once hoped.
Keywords: Truthfulness and falsehood -- Fiction; Secrecy -- Fiction; Friendship -- Fiction; Female friendship -- Fiction; Boarding schools -- Fiction; England -- Fiction; Thrillers (Fiction); Psychological fiction